2019
DOI: 10.1186/s12877-019-1151-x
|View full text |Cite
|
Sign up to set email alerts
|

Joint associations of smartphone use and gender on multidimensional cognitive health among community-dwelling older adults: a cross-sectional study

Abstract: Background Smartphone use has become an increasingly pervasive part of our daily lives, and as a portable media device, smartphones provide good support for cognitive training during aging. However, little is known about the joint association of smartphone use and gender on the cognitive health of older adults, particularly with regard to multi-domain cognition. Methods A face-to-face survey of 3230 older adults aged 60+ years was conducted in Xiamen, China, in 2016. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Being able to cue prospective tasks in a smartphone device, which would then offer auditory, tactile, and visual notifications—as opposed to paper-based calendars that offer only visual cues when or if a person views the calendar—removed the cognitive load associated with prospective memory ( El Haj et al, 2017 , 2021 ). Conversely, studies by Vaportzis, Martin et al (2017) and Yuan et al (2019) found no significant effects or interactions on memory abilities in older adults without cognitive impairment.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Being able to cue prospective tasks in a smartphone device, which would then offer auditory, tactile, and visual notifications—as opposed to paper-based calendars that offer only visual cues when or if a person views the calendar—removed the cognitive load associated with prospective memory ( El Haj et al, 2017 , 2021 ). Conversely, studies by Vaportzis, Martin et al (2017) and Yuan et al (2019) found no significant effects or interactions on memory abilities in older adults without cognitive impairment.…”
Section: Resultsmentioning
confidence: 82%
“…Improvements in assessment of executive functions, mental flexibility, attention, and language were also observed in participants with and without dementia ( Wu et al, 2019 ; Yuan et al, 2019 ). Yuan et al (2019) found that older adults without cognitive impairment who used more smartphone functions reported greater improvements in all cognitive domains than those who used fewer smartphone functions. Despite significant effects in some cognitive domains, Vaportzis, Martin et al (2017) reported no postintervention effects or interactions of tablet use on verbal comprehension or perceptual reasoning in cognitively healthy older adults.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…However, the prevalence of mobile phone usage in Chinese elderly people was unknown. A 2016 survey in Xiamen in China showed 30% of adults aged 60+ years used smartphones, and more functions were positively associated with increased general and partial subdomain cognitive functions [ 10 ]. Another small-scale, cross-sectional survey in China showed association between the usage of mobile phone and cognitive function [ 11 ].…”
Section: Introductionmentioning
confidence: 99%